2017
DOI: 10.1016/j.combustflame.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Thermal ignition revisited with two-dimensional molecular dynamics: Role of fluctuations in activated collisions

Abstract: The problem of thermal ignition in a homogeneous gas is revisited from a molecular dynamics perspective. A two-dimensional model is adopted, which assumes reactive disks of type A and B in a fixed domain that react to form type C products if an activation threshold for impact is surpassed. Such a reaction liberates kinetic energy to the product particles, representative of the heat release. The results for the ignition delay are compared with those obtained from the continuum description with the reaction rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…These do not have enough time to equilibrate with the rest of the system, thus giving rise to what we would like to call molecular hotspots. This result is also in accordance with the previous numerical results by Sirmas and Radulescu in the two-dimensional system [22]. In this regime of ignition, where non-equilibrium effects significantly promote ignition, we also observe a much higher stochasticity of ignition, as shown in Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These do not have enough time to equilibrate with the rest of the system, thus giving rise to what we would like to call molecular hotspots. This result is also in accordance with the previous numerical results by Sirmas and Radulescu in the two-dimensional system [22]. In this regime of ignition, where non-equilibrium effects significantly promote ignition, we also observe a much higher stochasticity of ignition, as shown in Fig.…”
Section: Resultssupporting
confidence: 93%
“…In our previous study, we compared the results only with reaction rate assuming homogenous ignition [22]. Whereas, in the present work along with the equilibrium reaction rate, we compared our results with the existing kinetic theory models which takes into account the effect of heat of reaction while calculating the reaction rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(19). This value is determined less by In a detonation, reaction might decouple from the shock and it has been found that the coherence and stability of a detonation are enhanced by low values of [67][68][69]. To this product can be added [2], the dimensionless gradient at a hot spot, and it follows that:…”
Section: Discussionmentioning
confidence: 99%